PROBLEM ITEMS OF FINANCIAL LITERACY ASSESMENT FOR STUDENTS IN LATVIA - Mihno, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Considering the financial situation in Latvia it is very important not only to realize how effectively students could deal with situations relating to financial issues, but to understand what kind of PISA Financial items exactly bring difficulties. It is necessary to realize how to improve students’ financial literacy. The main of the research is to find out what kind of PISA 2018 financial items are difficult for students and which students’ answers are marked as incorrect. To reach the aim the methods of content analysis. The research data show that students are very good at dealing with tasks similar to their everyday situations and requiring mathematical skills. In their turn, tasks related to investments and topics not related to everyday life are found difficult. Students are not good at tasks which require deep data or situation analysis and judgements made on reasoning even if they could be based on personal experience.